2018
DOI: 10.1080/00324728.2018.1493136
|View full text |Cite
|
Sign up to set email alerts
|

Mixed marriage among immigrants and their descendants in the United Kingdom: Analysis of longitudinal data with missing information

Abstract: This study investigates the formation of endogamous and exogamous marriages among immigrants and their descendants in the United Kingdom. We apply event history analysis to data from the Understanding Society study and use multiple imputation to determine the type of marriage for individuals with missing information on the origin of their spouse. The analysis shows, first, significant differences among immigrants and their descendants in the likelihood of marrying within and outside their ethnic groups. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…In some minority groups, exogamy can result in social exclusion or it can negatively impact the quality of family and other social contacts (Huijnk et al, 2010). Previous research has found that exogamy among immigrants is associated on the individual level with higher education, higher age, and higher-order unions; as well as with greater dissimilarities between the spouses with respect to age, education, religion, or other characteristics (Celikaksoy et al 2010;Fitzpatrick et al 2009;González-Ferrer et al 2018;Kalmijn, 1998;Kulu and Hannemann 2019;Troy et al 2006). These findings suggest that, on the one hand, exogamy may be a "second choice" that is made when individuals "cast a wider net" after searching for a longer time.…”
Section: Social Boundary Crossing In Mate Selectionmentioning
confidence: 99%
“…In some minority groups, exogamy can result in social exclusion or it can negatively impact the quality of family and other social contacts (Huijnk et al, 2010). Previous research has found that exogamy among immigrants is associated on the individual level with higher education, higher age, and higher-order unions; as well as with greater dissimilarities between the spouses with respect to age, education, religion, or other characteristics (Celikaksoy et al 2010;Fitzpatrick et al 2009;González-Ferrer et al 2018;Kalmijn, 1998;Kulu and Hannemann 2019;Troy et al 2006). These findings suggest that, on the one hand, exogamy may be a "second choice" that is made when individuals "cast a wider net" after searching for a longer time.…”
Section: Social Boundary Crossing In Mate Selectionmentioning
confidence: 99%
“…Lastly, the crucial role of human capital also emerged in other perspectives. Some studies (Lehrer 1998;van Tubergen/Maas 2007) showed that the most highly educated migrants are often encouraged to search for potential partners outside their own ethnic group.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This study uses data from seven European countries: the United Kingdom, France, Belgium, Switzerland, Estonia, Romania, and Spain. Prior to this study, five country case studies have been conducted that provide detailed analysis of inter-ethnic partnership in the United Kingdom, Spain, Estonia, Switzerland, and Romania (González-Ferrer et al 2016;Hărăguș 2016;Kulu and Hannemann 2018;Potârcă and Bernardi 2018;Puur et al 2018), which inspired the idea for this comparative paper. In order to make this paper even more representative of the European context, further research partners from France and Belgium were recruited to participate in this study.…”
Section: Included Countries and Samplingmentioning
confidence: 99%